Manipulation of Prenatal Thyroid Hormones Does Not Affect Growth or Physiology in Nestling Pied Flycatchers - Sarraude Tom; Hsu Bin-Yan; Groothuis Ton G. G.; Ruuskanen Suvi (UNIV CHICAGO PRESS, 2025)
Hormones transferred from mothers to their offspring are thought to be a tool for mothers to prepare their progeny for expected environmental conditions, thus increasing fitness. Thyroid hormones (THs) are crucial across vertebrates for embryonic and postnatal development and metabolism. Yet yolk THs have mostly been ignored in the context of hormone-mediated maternal effects. In addition, the few studies on maternal THs have yielded contrasting results that could be attributed to either species or environmental differences. In this study, we experimentally elevated yolk THs (within the natural range) in a wild population of a migratory passerine, the European pied flycatcher (Ficedula hypoleuca), and assessed the effects on hatching success, nestling survival, growth, and oxidative status (lipid peroxidation, antioxidant enzyme activity, and oxidative balance). We also sought to compare our results with those of a closely related species, the collared flycatcher (Ficedula albicolis), that has strong ecological and life-history similarities with our species. We found no effects of yolk THs on any of the responses measured. We could detect only a weak trend on growth: elevated yolk THs tended to increase growth during the second week after hatching. Our results contradict the findings of previous studies, including those of the collared flycatcher. However, differences in fledging success and nestling growth between both species in the same year suggest a context-dependent influence of the treatment. This study should stimulate more research on maternal effects mediated by THs and their potential context-dependent effects.